2007
DOI: 10.1534/genetics.107.075440
|View full text |Cite
|
Sign up to set email alerts
|

B Chromosome Polymorphism in Maize Landraces: Adaptivevs. Demographic Hypothesis of Clinal Variation

Abstract: Cytogenetic analysis of maize landraces from northwestern Argentina has revealed an altitudinal cline in the mean number of B chromosomes (B's) per plant, with cultivars growing at higher altitudes exhibiting a higher number of B's. Altitudinal and longitudinal clines are frequently interpreted as evidence of selection, however, they can also be produced by the interplay between drift and spatially restricted gene flow or by admixture between previously isolated populations that have come into secondary contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 65 publications
2
12
0
Order By: Relevance
“…Nonetheless, the pattern of observations is superficially consistent with a limit on maize GS as a function of elevation or variables correlated with elevation. We note that such limits on GS in maize have been argued previously based on the abundance of B chromosomes at different altitudes (Lia et al, 2007). …”
Section: Discussionsupporting
confidence: 73%
“…Nonetheless, the pattern of observations is superficially consistent with a limit on maize GS as a function of elevation or variables correlated with elevation. We note that such limits on GS in maize have been argued previously based on the abundance of B chromosomes at different altitudes (Lia et al, 2007). …”
Section: Discussionsupporting
confidence: 73%
“…In our study, the sequencing and alignment of fennel and carrot SSR loci revealed a general low degree of homology between the flanking regions and the repetitive motifs, and this could explain the observed low rates of transferability. Similar patterns of mutation, in terms of number of SSR repeat units, base substitution, and insertions/deletions (indels) within and outside the microsatellite motif were reported by other authors [68,69]. On the other hand, due to the lack of an EST-SSR bibliography in species closely related to fennel, we used genomic microsatellites known for their high polymorphism but low transferability, being slightly conserved.…”
Section: Discussionmentioning
confidence: 63%
“…[7,8,98]. Indeed, there are several cases of B polymorphisms whether numerical or structural [99,100]. For the B chromosome of the grasshopper E. plorans a large variety of structural variants has been demonstrated among many populations [99].…”
Section: Rapid Evolution Of Repeats On Bsmentioning
confidence: 99%